Risk of Disease Recurrence and Mortality Varies by Type of Fat Consumed before Cancer Treatment in a Longitudinal Cohort of Head and Neck Squamous Cell Carcinoma Patients. Issue 5 (16th February 2022) - Taha, Hania M; Rozek, Laura S; Chen, Xi; Li, Zonggui; Zarins, Katie R; Slade, Alexander N; Wolf, Gregory T; Arthur, Anna E
ABSTRACT: Background: The associations between specific types of fat and head and neck squamous cell carcinoma (HNSCC) recurrence and mortality rates have not yet been examined. Objectives: The purpose of this study was to determine how intakes of various fat subtypes before cancer treatment are associated with recurrence and mortality in adults diagnosed with HNSCC. Methods: This was a secondary analysis longitudinal cohort study of data collected from 476 newly diagnosed patients with HNSCC. Patients completed baseline FFQs and epidemiologic health surveys. Recurrence and mortality events were collected annually. Fat intakes examined included long-chain fatty acids (LCFAs), unsaturated fatty acids (FAs), PUFAs, ω-3 (n–3) PUFAs, ω-6 (n–6) PUFAs, MUFAs, animal fats, vegetable fats, saturated FAs, and trans fats. Associations between fat intake (categorized into tertiles) and time to event were tested using multivariable Cox proportional hazards models, adjusting for age, sex, smoking status, human papillomavirus status, tumor site, cancer stage, and total caloric intake. Intake of fats was compared with the lowest tertile. Results: During the study period, there were 115 recurrent and 211 death events. High LCFA intake was associated with a reduced all-cause mortality risk (HR: 0.55; 95% CI: 0.34, 0.91; P -trend = 0.02). High unsaturated FA intake was associated with a reduced all-cause mortality risk (HR: 0.62; 95% CI: 0.40, 0.97; P -trend = 0.04) and HNSCC-specific mortality risk (HR: 0.51; 95% CI: 0.29, 0.90; P -trend = 0.02). High intakes of ω-3 PUFAs (HR: 0.56; 95% CI: 0.35, 0.91; P -trend = 0.02) and ω-6 PUFAs (HR: 0.57; 95% CI: 0.34, 0.94; P -trend = 0.02) were significantly associated with a reduced all-cause mortality risk. There were no significant associations between other fat types and recurrence or mortality risk. Conclusions: In this prospective survival cohort of 476 newly diagnosed patients with HNSCC, our data suggest that HNSCC prognosis may vary depending on the fat types consumed before cancer treatment. Clinical intervention trials should test these associations.